Ruthenium(III) Catalysis in Perborate Oxidation of 5-Oxoacids. (24th August 2014) - Shree Devi, S.; Krishnamoorthy, P.; Muthukumaran, B.
Abstract : Ruthenium(III) catalyzes perborate oxidation of substituted 5-oxoacids in acidic solution. The catalyzed oxidation is first order with respect to the oxidant and catalyst. The rate of ruthenium(III) catalyzed oxidation displays the Michaelis-Menten kinetics on the reductant and is independent of [H + ] of the medium. Hydrogen peroxide is the reactive species of perborate and the kinetic results reveal formation of ruthenium(III) peroxo species-5-oxoacid complex. Electron-releasing substituents accelerate the reaction rate and electron-withdrawing substituents retard it. The order of reactivity among the studied 5-oxoacids is p -methoxy≫    p -methyl > p -phenyl > −H > p -chloro > p -bromo > m -nitro. Activation parameters are evaluated using Arrhenius and Eyring's plots. A mechanism consistent with the observed kinetic data is proposed and discussed. A suitable rate law is derived based on the mechanism.